(untitled) (Hackensack, N.J., 2005)
This comprehensive volume presents invited reviews and short notes with exciting new results obtained in fabrication study and application of nanostructures, which promise a new generation of electronic and optoelectronic devices. The rapid progress in nanoelectronics and optoelectronics, molecular electronics and spintronics, nanotechnology and quantum processing of information are covered.
Keywords: Nanostructures,Solid state chemistry,Nanotechnology,Nanostructures; Industrial applications,Cấu trúc nano,Công nghệ nano,Hóa học chất rắn; Ứng dụng công nghiệp